Analysis of Stability of Traveling Wave for Kadomtsev-Petviashvili Equation - Jun Liu; Xi Liu; Gui Mu; Chunyan Zhu; Jie Fu (Abstract and Applied Analysis)
This paper presents the boundedness and uniform boundedness of traveling wave solutions for the Kadomtsev-Petviashvili (KP) equation. They are discussed by means of a traveling wave transformation and Lyapunov function.